Anticancer effect of (S)-crizotinib on osteosarcoma cells by targeting MTH1 and activating reactive oxygen species. Issue 4 (April 2018) - Qing, Xiangcheng; Shao, Zengwu; Lv, Xiao; Pu, Feifei; Gao, Feng; Liu, Lei; Shi, Deyao
Abstract : MTH1 has become a new rising star in the field of 'cancer phenotypic lethality' and can be targeted in many kinds of tumors. This study aimed to explore the anticancer effect of MTH1-targeted drug (S)-crizotinib on osteosarcoma (OS) cells. We detected MTH1 expression in OS tissues and cells using immunohistochemistry and western blot. The effects of MTH1 on OS cell viability were explored using the siRNA technique and CCK8. The anticancer effects of the MTH1-targeted drug (S)-crizotinib on OS cells were explored by in-vitro assays. The intracellular 8-oxo-dGTP level and oxygen reactive species (ROS) of OS cells were detected by Cy3-conjugated avidin staining and dichlorofluorescein diacetate staining, respectively. The expression of MTH1 was significantly higher in OS tissues and cell lines than that in the corresponding adjacent tissues and osteoblastic cell line. The proliferation of OS cells was significantly inhibited through knockdown of MTH1 by siRNA technology. (S)-Crizotinib could inhibit the proliferation of OS cells with an increase in the apoptosis levels and causing G0/G1 arrest by targeting MTH1 and activating ROS. In addition, (S)-crizotinib could inhibit the migration of OS cells. (S)-Crizotinib could suppress the proliferation and migration, cause G0/G1 arrest, and increase the apoptosis level of OS cells by targeting MTH1 and activating ROS. This study will provide a promising therapeutic target and the theoretical basis for the clinical application of (S)-crizotinib in OS.